Enrichment of nanofiber hydrogel composite with fractionated fat promotes regenerative macrophage polarization and vascularization for soft-tissue engineering - Henn, Dominic; Fischer, Katharina S.; Chen, Kellen; Greco, Autumn H.; Martin, Russell A.; Sivaraj, Dharshan; Trotsyuk, Artem A.; Mao, Hai-Quan; Reddy, Sashank K.; Kneser, Ulrich; Gurtner, Geoffrey C.; Schmidt, Volker-Jürgen; et al. (Plastic and reconstructive surgery, 2022)
Background: - Fractionated fat has been shown to promote dermal regeneration; however, the use of fat grafting for reconstruction of soft-tissue defects is limited because of volume loss over time. The authors have developed a novel approach for engineering of vascularized soft tissue using an injectable nanofiber hydrogel composite enriched with fractionated fat. - Methods: - Fractionated fat was generated by emulsification of groin fat pads from rats and mixed in a 3:1 ratio with nanofiber hydrogel composite (nanofiber hydrogel composite with fractionated fat). Nanofiber hydrogel composite with fractionated fat or nanofiber hydrogel composite alone was placed into isolation chambers together with arteriovenous loops, which were subcutaneously implanted into the groin of rats (n = 8 per group). After 21 days, animals were euthanized and systemically perfused with ink, and tissue was explanted for histologic analysis. Immunofluorescent staining and confocal laser scanning microscopy were used to quantify CD34+ progenitor cell and macrophage subpopulations. - Results: - Nanofiber hydrogel composite with fractionated fat tissue maintained its shape without shrinking and showed a significantly stronger functional vascularization compared to composite alone after 21 days of implantation (mean vessel count, 833.5 ± 206.1 versus 296.5 ± 114.1; p = 0.04). Tissue heterogeneity and cell count were greater in composite with fractionated fat (mean cell count, 49,707 ± 18,491 versus 9263 ± 3790; p = 0.005), with a significantly higher number of progenitor cells and regenerative CD163+ macrophages compared to composite alone. - Conclusions: - Fractionated fat-enriched nanofiber hydrogel composite transforms into highly vascularized soft tissue over 21 days without signs of shrinking and promotes macrophage polarization toward regenerative phenotypes. Enrichment of injectable nanofiber hydrogel composite with fractionated fat represents a promising approach for durable reconstruction of soft-tissue defects. - Clinical Relevance Statement: - The authors' approach for tissue engineering may ultimately lay the groundwork for clinically relevant applications with the goal of generating large volumes of vascularized soft tissue for defect reconstruction without donor site morbidity.
Gesehen am 02.06.2022